European Community and multinational enterprises : lessons in the social control of industry. - Scaperlanda, Anthony (1992)
Looks at the technological forces that underpin the evolving economic, social, and political environment in the European Community. Controls such as the regulation of large mergers, encouragment to small- and medium-sized enterprises, dimished barriers to trade, as well as training programmes, environmental standards and worker participation in decision making have been set up to ensure a balanced approach to controlling intra-EC multinational enterprises.